Learning by doing: enhancing hydrology lectures with individual fieldwork projects. Issue 2 (3rd April 2019) - Van Loon, Anne F.
ABSTRACT: Hydrology teaching deals with processes happening outside the classroom, which calls for active-learning methods to complement lectures. In a geography undergraduate course, new teaching methods and assessment were designed, in which students investigated a river of their choice by completing homework tasks and presenting their results on a poster. During a 3-year implementation process, the changes were evaluated using a combination of formal and informal student and lecturer feedback. Students mentioned that they enjoyed doing the project and that it helped their understanding of theory, their research skills, and their ability to select, organize and present information. Questionnaire results showed that, over the implementation period, students' perceived value of homework increased strongly, while their perceived value of lectures remained high. In informal feedback, students noted that they enjoyed learning about where they live, preferred doing the projects individually and seeing each other's projects, and spent more time on the coursework when assessed. When looking back in interviews, students commented that the projects had prepared them well for their dissertation and summer job. The advantage of using homework-based projects complementing lectures is the strong link between theory and practice, which could be further enhanced by discussing the homework in the lectures.